1997
DOI: 10.1159/000011833
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pilot Study of Intrahepatic Arterial Chemotherapy with Methotrexate, 5-Fluorouracil, Cisplatin and Subcutaneous Interferon-Alpha-2b for Patients with Locally Advanced Hepatocellular Carcinoma

Abstract: To evaluate the efficacy of methotrexate (MTX)-5-fluorouracil (5-FU), cisplatin (CDDP), and interferon-α-2b(IFNα-2b) combination therapy, we conducted a clinical pilot study in patients with locally advanced hepatocellular carcinoma (HCC). Sixteen patients, who had received no prior treatment for the HCC, with portal tumor thrombosis in the main trunk or in the major branch were enrolled in the study. IFNα-2b (3 × 106 units) was injected subcutaneously 3 times per week. After a bolus administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 20 publications
4
65
1
Order By: Relevance
“…thrombi in the major branches of the portal vein (Vp3 or 4), as our second report on this treatment. The efficacy of such treatment was 43.6% in our patients with highly advanced HCC, which was almost similar to the previous report of patients with the same stage HCC (Urabe et al, 1998). The prognosis of such patients is extremely poor and survival is generally limited to a few months after diagnosis, despite multimodal therapies even in cases suitable Figure 3 Immunohistochemical analysis of IFNAR2 expression in HCC tissues.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…thrombi in the major branches of the portal vein (Vp3 or 4), as our second report on this treatment. The efficacy of such treatment was 43.6% in our patients with highly advanced HCC, which was almost similar to the previous report of patients with the same stage HCC (Urabe et al, 1998). The prognosis of such patients is extremely poor and survival is generally limited to a few months after diagnosis, despite multimodal therapies even in cases suitable Figure 3 Immunohistochemical analysis of IFNAR2 expression in HCC tissues.…”
Section: Discussionsupporting
confidence: 88%
“…Patt et al (1993) reported 31% response rate in patients with unresectable advanced hepatoma and low alpha-fetoprotein (AFP) levels. Using intra-arterial infusion chemotherapy and systemic IFN-a, Urabe et al (1998) reported a response rate of 47% in patients with Vp3. In another study, Leung et al (1999) used cisplatin, doxorubicin, and IFN-a and reported that this treatment converted nine patients of 36 patients with inoperable HCC to become suitable for tumour resection, and none developed postoperative recurrence.…”
mentioning
confidence: 99%
“…The poor results may be the result of the huge tumor burden in the studies. [25][26][27][28] It has been postulated that postoperative adjuvant IFNs may inhibit the recurrence of HCC after operation. 29 In this study, therefore, the authors investigated the preventive benefit of IFN-␣ in inhibition of tumor growth and recurrence after curative resection in LCI-D20 model, with potential minimum tumor burden, at maximum tolerated doses for long duration (at daily dose of 3 ϫ 10 7 U/kg for 35 days).…”
Section: Discussionmentioning
confidence: 99%
“…The response rate of advanced HCC to HAIC is approximately 30-40% (9)(10)(11)(12)(13)(14)(15)(16), and HAIC (as well as sorafenib) is recommended for treatment of advanced HCC, particularly in Japan (17,18). However, comparison of the effects of sorafenib with other treatment methods for HCC has not been Sorafenib and hepatic arterial infusion chemotherapy for unresectable advanced hepatocellular carcinoma: A comparative study carried out.…”
Section: Introductionmentioning
confidence: 99%